A vacuum switch copper-chromium series contact material and its preparation process and device

The copper-chromium series contact material preparation process addresses the limitations of existing methods by incorporating Cr and W powders with gradient temperature sintering and controlled cooling, enhancing resistance and mechanical properties for high-voltage vacuum switches.

CN118792533BActive Publication Date: 2024-12-13陕西陕煤启远科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411270383.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-13
Estimated Expiration
2044-09-11

AI Technical Summary

Technical Problem

Current processes for preparing copper-chromium series contact materials for vacuum switches fail to simultaneously improve pressure resistance, ablation resistance, and welding resistance, leading to issues such as component segregation, uneven composition, and reduced mechanical properties.

Method used

A preparation process involving mixing Cr and W powders, followed by solid-phase and liquid-phase sintering with gradient temperature increases, directional cooling, and subsequent solution and aging treatments to create a copper-infiltrated chromium-tungsten material with controlled solidification.

Benefits of technology

The process results in a contact material with high density, improved ablation and welding resistance, and reduced internal defects, suitable for high-voltage vacuum switches.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118792533B_ABST
    Figure CN118792533B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of metal composite material preparation, and relates to a vacuum switch copper-chromium series contact material and its preparation process and device. The preparation process is specifically as follows: solid-phase sintering of Cr powder and W powder into a chromium-tungsten skeleton, and then liquid-phase sintering to obtain a copper-chromium-tungsten infiltrated material; gradually reducing the cooling temperature of the copper-chromium-tungsten infiltrated material to form a gradient temperature field distribution in which the temperature gradually decreases from the top to the bottom of the material, and the copper liquid above the copper-chromium-tungsten infiltrated material continues to flow from the top to the bottom, so that the copper liquid gradually solidifies from the bottom to the top; finally, after solid solution treatment and aging treatment, the vacuum switch copper-chromium series contact material is obtained. Also disclosed is a device for realizing the preparation process, wherein the furnace body is provided with a lifting mechanism, and during the solidification process, the lifting mechanism is adjusted to gradually descend, so that the material gradually solidifies from the bottom to the top, and it is ensured that there is always copper liquid replenished above during the solidification process, so that the prepared material has the least internal pores, the highest density, and improved pressure resistance, and can be applied to high-voltage vacuum switches.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal composite material preparation, and in particular relates to a vacuum switch copper-chromium series contact material and a preparation process and device thereof. Background Art

[0002] As 72.5Kv, 126Kv, and 252Kv SF6 switches are gradually replaced by vacuum switches (the greenhouse effect of SF6 gas is 23,900 times that of CO2), the development of high-voltage and ultra-high-voltage vacuum switches has become one of the hot spots in electrical equipment. Copper-chromium series contact materials are the main materials for vacuum switches. In high-voltage and high-current environments, there are high requirements for the pressure resistance, ablation resistance, and welding resistance of the contact materials.

[0003] At present, the processes that can be used to batch prepare copper-chromium series contact materials include powder metallurgy, vacuum melting and arc melting. Powder metallurgy is a solid-solid sintering method, which is to mix copper powder and chromium powder fully and then sinter them in a vacuum sintering furnace to prepare contact materials. The contact materials prepared by this method have low density (density ≤ 99.5%) and can only be used in vacuum switches with a voltage level of 12Kv, but not in vacuum switches with high voltage levels. The vacuum melting method is a method for preparing composite materials by liquid-liquid sintering. Chromium and copper are melted in a vacuum environment and then cast to prepare a copper-chromium alloy material. According to the copper-chromium binary alloy phase diagram, when the chromium content is ≥40%, the solid solubility of chromium in copper is extremely low. Therefore, component segregation is likely to occur after casting, and it can only be used in vacuum switches below 40.5KV; the composition is uneven, the tissue defects increase, and breakdown is likely to occur in uneven local areas, resulting in poor pressure resistance; component segregation may lead to insufficient chromium content in certain areas, thereby reducing the material's ablation resistance; it may also lead to reduced mechanical properties of the material and poor resistance to fusion welding in weak locations. Arc melting is an improved process of vacuum melting. Electrode rods are made of copper powder and chromium powder, and then the electrode rods are melted layer by layer by electric arc. The molten solution is quickly cooled through a crystallizer to prevent the segregation of copper-chromium materials. This method can be used to prepare contact materials with high chromium content, but chromium is melted many times during the preparation process, which greatly reduces the Gibbs free energy of chromium, reduces the resistance of copper-chromium contact materials to welding, and is prone to adhesion during use. It can only be used in vacuum switches below 40.5KV.

[0004] In summary, the current process for preparing copper-chromium series contact materials cannot simultaneously improve the pressure resistance, ablation resistance and welding resistance of the copper-chromium contact materials. Summary of the invention

[0005] One of the purposes of the present invention is to provide a vacuum switch copper-chromium series contact material and a preparation process thereof, which solves the problem that the existing process cannot simultaneously improve the pressure resistance, ablation resistance and welding resistance of the copper-chromium contact material.

[0006] The second object of the present invention is to provide a device for realizing the preparation process of copper-chromium series contact materials for vacuum switches.

[0007] The present invention is achieved through the following technical solutions:

[0008] The invention discloses a preparation process of a copper-chromium series contact material for a vacuum switch, comprising the following steps:

[0009] (1) Mixing: In a vacuum environment, Cr powder and W powder are mixed into a mixture; wherein the Cr powder and W powder are mixed according to the weight percentage of Cr powder 99.0% to 99.5% and W powder 0.5% to 1%;

[0010] (2) Solid-phase sintering: The mixed material is subjected to solid-phase sintering treatment and then naturally cooled to obtain a chromium-tungsten skeleton; wherein the solid-phase sintering treatment adopts a gradient temperature increase;

[0011] (3) Liquid phase sintering: placing an oxygen-free copper rod on a chromium-tungsten skeleton and performing liquid phase sintering treatment to allow the copper liquid to infiltrate the chromium-tungsten skeleton to obtain a copper-infiltrated chromium-tungsten material; wherein the liquid phase sintering treatment adopts a gradient temperature increase;

[0012] (4) Directional cooling and solidification: gradually reduce the cooling temperature of the copper-chromium-tungsten infiltrated material, forming a gradient temperature field distribution in which the temperature gradually decreases from the top to the bottom of the copper-chromium-tungsten infiltrated material; at the same time, the copper liquid above the copper-chromium-tungsten infiltrated material continues to flow from the top to the bottom, so that the copper liquid gradually solidifies from the bottom to the top;

[0013] (5) Subsequent treatment: The material after the cooling and solidification treatment in step (4) is subjected to solution treatment and aging treatment in sequence to obtain a vacuum switch copper-chromium series contact material.

[0014] Preferably, in step (1), when preparing the Cr powder and the W powder, the ingredients are first dried under vacuum conditions, and then the dried ingredients are mixed and stirred to obtain a mixture.

[0015] Preferably, a porous crucible is used to load the mixture. The porous structure of the porous crucible allows gas to freely flow in and out during the sintering process, which helps to remove volatile impurities in the mixture and gases generated by the reaction, thereby improving the purity and quality of the product.

[0016] Preferably, the ingredients are dried under vacuum conditions, specifically:

[0017] Place the ingredients in a vacuum drying oven, start heating when the vacuum degree is ≤-0.08MPa, heat to 60-85℃, and keep warm for 3-6h.

[0018] Preferably, in step (2), the solid phase sintering process adopts a gradient temperature increase, and the specific operation is as follows:

[0019] Raise the temperature from room temperature to 200-250°C within 45-60 minutes; continue to raise the temperature to 600-650°C within 60-90 minutes, and keep it warm for 45-60 minutes; continue to raise the temperature to 850-950°C within 60-90 minutes, and keep it warm for 90-120 minutes.

[0020] Preferably, in step (2), during the solid phase sintering process, the vacuum degree is required to be ≤10 -1 Pa.

[0021] Preferably, the oxygen-free copper rod is pretreated, specifically:

[0022] Cut the oxygen-free copper rod into a length of 1 / 2 of the hole depth of the porous crucible, wipe the surface of the oxygen-free copper rod clean, and dry it in a vacuum drying oven for 3-6 hours at a drying temperature of 60-85°C.

[0023] Preferably, a dried oxygen-free copper rod is placed on a fired chromium-tungsten skeleton, and a graphite paper is covered on the porous crucible to prevent copper from volatilizing.

[0024] Furthermore, in step (3), the liquid phase sintering process adopts a gradient temperature increase, and the specific operation is as follows:

[0025] The temperature after cooling from solid phase sintering is raised to 800-900°C within 120-150 minutes, and kept at this temperature for 60-90 minutes; the temperature is further raised to 1300-1480°C within 60-90 minutes, and kept at this temperature for 90-150 minutes.

[0026] Furthermore, in step (4), the vacuum degree during the cooling and solidification process is required to be ≤5x10 -2 Pa.

[0027] Furthermore, in step (5), the specific operation of the solution treatment is:

[0028] The solution temperature is 920-980℃, the holding time is 120-240min, and air cooling is used.

[0029] Furthermore, in step (5), the specific operation of the aging treatment is:

[0030] The aging temperature is 420-480℃, the holding time is 180-360min, and the cooling is done in air.

[0031] The present invention also discloses a vacuum switch copper-chromium series contact material prepared by the preparation process, wherein the density of the vacuum switch copper-chromium series contact material is 7.95-8.05 g / cm 3 The average hardness is 85-108HB, the conductivity is 16.3-22.4MS / m, and the density is over 99%.

[0032] The present invention also discloses a device for realizing the preparation process, comprising a furnace body, wherein the furnace body is provided with a lifting mechanism, a material rack and a heat insulation board;

[0033] The lifting mechanism includes a driving source and a lifting rod, the upper end of the lifting rod is connected to the material rack, and the lower end is connected to the driving source;

[0034] The furnace body is divided into a heating and heat preservation zone at the top and a cooling zone at the bottom by a heat insulation plate;

[0035] When in use, during the solid phase sintering stage and the liquid phase sintering stage, the material on the rack is located in the heating and heat preservation zone; during the directional cooling and solidification stage, the lifting mechanism descends and the material on the rack is located in the cooling zone;

[0036] The lifting mechanism is controlled to descend gradually in multiple times to gradually reduce the cooling temperature of the copper-chromium-tungsten infiltrated material. Each time it descends to a certain height, it stays there for a period of time before descending again.

[0037] Compared with the prior art, the present invention has the following beneficial technical effects:

[0038] The preparation process of the copper-chromium series contact material for vacuum switches disclosed in the present invention has the following advantages:

[0039] On the one hand, when selecting raw materials, Cr powder and W powder are used to prepare the mixture. The addition of W element can limit the growth of Cr particles, thereby achieving the purpose of refining particles; however, when the amount of W element added is too low, the hardness of the prepared contact material will be very low, and the purpose of improving the ablation resistance of the material cannot be achieved. If the amount of W added is too large, the conductivity of the contact material will be affected. Too low conductivity will cause a large temperature rise of the contact material during the use of the circuit breaker. Through design research, the present invention has repeatedly studied and determined the addition ratio of W powder to be 0.5%~1%. In this way, the introduced W element is only a trace amount, which can effectively improve the ablation resistance of the material without causing component segregation.

[0040] On the other hand, gradient temperature rise is used for heating in both solid-phase sintering and liquid-phase sintering processes. The purpose of gradient temperature rise in solid-phase sintering is to sinter a chromium-tungsten skeleton with a low gas content. In this stage, a skeleton with a certain strength will be formed between the chromium powder and the tungsten powder under the action of pressure and temperature. In the liquid-phase sintering process, the gradient temperature rise is a skeleton preheating and degassing process at the beginning of heating, and the subsequent heating is a copper infiltration process, so that the copper liquid infiltrates into the chromium-tungsten skeleton under vacuum.

[0041] What is particularly important and also reflects the core invention of the present invention is that in the cooling and solidification stage, the existing solidification process adopts natural cooling. This treatment method will increase the internal defects of the material and reduce the yield of the material preparation. In the cooling and solidification stage, the present invention gradually reduces the cooling temperature of the copper-chromium-tungsten infiltrated material to form a gradient temperature field distribution in which the temperature gradually decreases from the top to the bottom of the material. The copper liquid at the bottom of the copper-chromium-tungsten infiltrated material solidifies first, so that the copper liquid is always replenished above the solidification area during the solidification process. The purpose is to allow the material to solidify gradually from the bottom to the top, and then control the solidification direction of the copper liquid in the copper-chromium-tungsten infiltrated material, avoiding material defects that may occur during the cooling and solidification process. The material prepared in this way has fewer internal pores, high density, and improved pressure resistance, and can be applied to high-voltage vacuum switches.

[0042] In summary, the present invention improves the ablation resistance of the material by adding trace elements W, and improves the material's resistance to welding by sintering the chromium tungsten skeleton through two gradient temperature rise treatments. In particular, the directional cooling and solidification treatment can reduce the defects, pores and inclusions generated in the material preparation process, effectively control the possible defects of the material, and improve the pressure resistance of the material.

[0043] Furthermore, when Cr powder and W powder are prepared, the ingredients are dried to remove moisture in the ingredients and prevent the raw materials from agglomerating and mixing unevenly during the mixing process.

[0044] Furthermore, a gradient heating method is adopted in the solid-phase sintering stage. In the first stage, the temperature is rapidly heated to 200-250°C. The purpose is to preheat the powder and remove moisture from the chromium tungsten powder. Because at 200-250 degrees, moisture can escape from the powder and be pumped out of the furnace by a vacuum pump; the second stage is the degassing process, which is heated to 600-650°C. At this time, the gas attached to the surface of the chromium powder and tungsten powder will escape and be pumped out by a vacuum pump. This process is the key to sintering a skeleton with low gas content; the third stage is heated to 850-950°C. At this stage, a skeleton with a certain strength will be formed between the chromium powder and the tungsten powder under pressure and temperature. If the temperature is too low, the strength of the skeleton is insufficient; if the temperature is too high, the porosity of the skeleton cannot be guaranteed, resulting in the subsequent preparation of the material composition not meeting the requirements.

[0045] Furthermore, during the firing of the chromium-tungsten skeleton, the vacuum degree in the furnace is required to be 10 -1 Below Pa, if it is higher than this value, the skeleton is easily oxidized, resulting in poor wettability of the copper and chromium-tungsten skeletons, and the appearance of chromium-rich, pores and inclusion defects.

[0046] Furthermore, the chromium tungsten skeleton and oxygen-free copper rod are liquid-phase sintered by a gradient temperature increase method. The first stage of heating at 800-900°C is the skeleton preheating and degassing process, and the second stage of heating at 1300-1480°C is the copper infiltration process, so that the copper liquid infiltrates into the chromium tungsten skeleton under vacuum.

[0047] Furthermore, during the solidification process, the vacuum degree in the furnace is required to be 5x10 -2 Below Pa. If it is higher than this value, the gas content of the prepared copper-chromium contact material will easily exceed the requirements of the national standard and enterprise standard for the gas content of the contact material.

[0048] The present invention also discloses a device for realizing the above-mentioned preparation process. A lifting mechanism is provided under the material rack in the furnace body, and the furnace body is divided into a heating and heat preservation zone at the upper part and a cooling zone at the lower part by a heat insulation plate. In the solid phase sintering and liquid phase sintering stages, the lifting mechanism drives the material rack to rise to the heating and heat preservation zone; in the solidification stage, the lifting mechanism gradually descends, driving the material rack to descend to the cooling zone. The upper part of the copper-chromium-tungsten infiltrated material is close to the heating zone, and the lower part is far away from the heating zone, which results in a gradient temperature field distribution with gradually decreasing temperature from the top to the bottom of the copper-chromium-tungsten infiltrated material. The copper liquid gradually solidifies from the bottom to the top, and the solidification direction of the copper liquid can be directionally controlled. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 A schematic diagram of the device structure for realizing the preparation process of the copper-chromium series contact material of the vacuum switch of the present invention;

[0050] Among them, 1. furnace body; 2. driving source; 3. lifting rod; 4. material rack; 5. heat insulation board. DETAILED DESCRIPTION

[0051] In order to make the purpose, technical scheme and advantages of the present invention clearer, the following is further described in detail with reference to the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention, that is, the embodiments described are only part of the embodiments of the present invention, rather than all the embodiments.

[0052] The detailed description of the embodiments of the present invention provided below is not intended to limit the scope of the invention claimed for protection, but merely represents a selected embodiment of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of the present invention.

[0053] The invention discloses a preparation process of a copper-chromium series contact material for a vacuum switch, comprising the following steps:

[0054] (1) Preparation of materials

[0055] Cr powder and tungsten powder are selected: Cr powder purity ≥99.50%, mesh number 80-200; W powder purity ≥99.0%, mesh number 180-300.

[0056] Cr powder and W powder are mixed according to the weight percentage of Cr (99.0~99.5) wt.%, W (0.5~1) wt.% to obtain a mixture.

[0057] (2) Solid phase sintering

[0058] The mixed powder is loosely loaded into the holes of the porous crucible, and then the powder-loaded crucible is placed on a powder vibrator for compaction; the chromium-tungsten skeleton is sintered by a gradient heating method, and the sintering temperature is as follows:

[0059] Raise the temperature to 200-250℃ within 45-60min; continue to raise the temperature to 600-650℃ within 60-90min, and keep warm for 45-60min; continue to raise the temperature to 850-950℃ within 60-90min, and keep warm for 90-120min.

[0060] (3) Liquid phase sintering

[0061] Placing an oxygen-free copper rod on a chromium-tungsten skeleton and performing a liquid phase sintering treatment to allow the copper liquid to infiltrate the chromium-tungsten skeleton to obtain a copper-infiltrated chromium-tungsten material; wherein the liquid phase sintering treatment adopts a gradient temperature increase;

[0062] The temperature curve of the gradient heating is as follows: the temperature after cooling from solid phase sintering is raised to 800-900°C within 120-150min, and kept warm for 60-90min; the temperature is further raised to 1300-1480°C within 60-90min, and kept warm for 90-150min.

[0063] (4) Directional cooling solidification

[0064] After liquid phase sintering, the cooling temperature of the copper-chromium-tungsten infiltrated material is controlled to gradually decrease, so that the copper-chromium-tungsten infiltrated material forms a gradient temperature field distribution with the temperature gradually decreasing from top to bottom. The copper liquid at the bottom of the copper-chromium-tungsten infiltrated material solidifies first, and the copper liquid above the solidification area will be replenished downward, so that the copper liquid gradually solidifies from the bottom to the top, reducing the appearance of voids and realizing the control of the solidification direction of the copper liquid in the copper-chromium-tungsten infiltrated material.

[0065] (5) Solution treatment and aging treatment

[0066] Firstly, the prepared rods are placed in the No. 1 heat treatment furnace for solution treatment at a solution temperature of 920-980°C, kept warm for 120-240 minutes, and air-cooled with the furnace. Then, the rods are placed in the No. 2 heat treatment furnace for aging treatment at a heating temperature of 420-480°C, kept warm for 180-360 minutes, and cooled with the furnace. Finally, a vacuum switch copper-chromium series contact material with high density, low gas content, strong resistance to ablation and welding is obtained.

[0067] More preferably, in step (1), the ingredients are dried in a vacuum drying oven, and heating is started when the vacuum degree is ≤-0.08MPa, and the temperature is heated to 60-85°C and kept warm for 3-6h.

[0068] Load the dried ingredients into a double-motion mixer and mix them at a stirring speed of 50-80 r / min for 3-6 hours. After mixing, store the mixture in a vacuum drying oven.

[0069] In order to better control the directional cooling solidification in the solidification stage, the present invention also designs a device such as Figure 1 As shown, the furnace body 1 includes a lifting mechanism, a material rack 4 and a heat insulation board 5; the lifting mechanism includes a driving source 2 and a lifting rod 3, the upper end of the lifting rod 3 is connected to the material rack 4, and the lower end is connected to the driving source 2; the furnace body 1 is divided into a heating and heat preservation zone located at the upper part and a cooling zone located at the lower part by the heat insulation board 5. When heating is required, the lifting mechanism drives the material rack 4 to rise to the heating and heat preservation zone, and when cooling is required, the lifting mechanism drives the material rack 4 to descend to the cooling zone. The structure is simple and can better control the heating and cooling process. Especially in the solidification process, the lifting mechanism gradually descends, and each time it descends a certain distance, which well controls the solidification direction of the material.

[0070] Specifically, the driving source 2 may be a motor, a cylinder, a hydraulic cylinder, or the like.

[0071] The implementation steps of the present invention are further described below in conjunction with specific implementation methods to reflect the advantages of using this method to prepare materials.

[0072] Example 1

[0073] (1) Preparation of materials

[0074] Take Cr powder with a purity of ≥99.50% and a mesh size of 80-200 and W powder with a purity of ≥99.0% and a mesh size of 180-300, mix them in a ratio of 99:1, put the ingredients in a vacuum drying oven, pump the vacuum degree to -0.085MPa, start heating to 60℃, and keep it warm for 6h. Put the dried ingredients into a mixer at a speed of 50r / min, stir and mix for 6h to obtain a mixture.

[0075] (2) Solid phase sintering

[0076] Take a graphite crucible with a diameter of Ф460mm and an aperture of 48mm. The crucible height is 240mm, and the graphite crucible is cleaned. The mixture prepared in step 1 is loaded into the hole of the graphite crucible using a funnel. The loose height is 120mm. The graphite crucible filled with powder is placed on a vibrator with an amplitude set to 1mm and a powder vibration time set to 120s.

[0077] Place the graphite crucible on the rack 4 of the device, turn on the slide valve pump and the Roots pump, and when the vacuum degree is 6.2x10 -2 Start heating at Pa, and raise the temperature from room temperature to 200℃ within 45min; continue to raise the temperature from 200℃ to 600℃ within 60min, and keep it warm for 45min; continue to raise the temperature from 600℃ to 850℃ within 60min, and keep it warm for 90min; after heating, lower the lifting mechanism to the cooling zone, and open the furnace door as the furnace naturally cools to below 100℃.

[0078] (3) Liquid phase sintering

[0079] Take an oxygen-free copper rod with a diameter of 46 and a material of TU0, cut it into a length of 1 / 2 of the crucible hole depth, wipe the surface of the copper rod clean with alcohol, and place it in a vacuum drying oven for 6 hours at a drying temperature of 60°C. Place the baked copper rod on the fired skeleton, and cover the crucible with graphite paper to prevent copper volatilization. Use a lifting mechanism to raise the graphite crucible to the insulation zone, and use a gradient heating method for liquid phase sintering. The temperature curve is as follows: within 120 minutes, the temperature after cooling from solid phase sintering is raised to 800°C, and the temperature is kept for 60 minutes; within 60 minutes, the temperature is continued to rise to 1300°C, and the temperature is kept for 90 minutes.

[0080] (4) Directional cooling solidification

[0081] After liquid phase sintering is completed, the solidification direction of the material is controlled by adjusting the height of the lifting mechanism. The specific implementation method is as follows:

[0082] The lifting mechanism descends 50mm and maintains for 30 minutes;

[0083] The lifting mechanism continues to descend 50mm and maintains this position for 30 minutes;

[0084] The lifting mechanism continues to descend 50 mm and maintains this position for 60 minutes;

[0085] The lifting mechanism continues to descend 100 mm, and the prepared rods are taken out as the furnace naturally cools to below 100°C.

[0086] The vacuum degree in the furnace during solidification should be ≤5x10 -2 Pa.

[0087] (5) Solution treatment and aging treatment

[0088] First, the prepared bar material was placed in the No. 1 heat treatment furnace for solution treatment at a temperature of 920°C, kept at this temperature for 120 minutes, and then air-cooled with the furnace;

[0089] The rods were then placed in a No. 2 heat treatment furnace for aging treatment at a heating temperature of 420°C and a holding time of 180 minutes. The materials were cooled in the furnace and finally a vacuum switch copper-chromium series contact material with high density, low gas content, and strong resistance to ablation and welding was obtained.

[0090] Example 2

[0091] (1) Preparation of materials

[0092] Take Cr powder with a purity of ≥99.50% and a mesh size of 80-200 and W powder with a purity of ≥99.0% and a mesh size of 180-300, mix them according to 99.5:0.5, put the ingredients in a vacuum drying oven, draw the vacuum degree to -0.088MPa, heat to 60℃, and keep warm for 6h. Put the dried ingredients into a mixer at a speed of 50r / min, stir and mix for 6h to obtain a mixture.

[0093] (2) Solid phase sintering

[0094] Take a graphite crucible with a diameter of 460mm and a hole diameter of 48mm. The crucible height is 240mm, and the crucible is cleaned. The mixture prepared in step 1 is loaded into the hole of the crucible using a funnel. The loose height is 120mm. The powder-filled crucible is placed on a vibrator with an amplitude set to 1mm and a powder vibration time set to 120s.

[0095] Place the graphite crucible on the rack 4 of the device, turn on the slide valve pump and the Roots pump, and when the vacuum degree is 8.4x10 -2 Start heating at Pa, and raise the temperature from room temperature to 200℃ within 45min; continue to raise the temperature from 200℃ to 600℃ within 60min, and keep it warm for 45min; continue to raise the temperature from 600℃ to 850℃ within 60min, and keep it warm for 90min; after heating, lower the lifting mechanism to the cooling zone, and open the furnace door as the furnace naturally cools to below 100℃.

[0096] (3) Liquid phase sintering

[0097] Take an oxygen-free copper rod with a diameter of 46 and a material of TU0, cut it into a length of 1 / 2 of the crucible hole depth, wipe the surface of the copper rod clean with alcohol, and place it in a vacuum drying oven for 6 hours at a drying temperature of 60°C. Place the baked copper rod on the fired skeleton, and cover the crucible with graphite paper to prevent copper from volatilizing. Use a lifting mechanism to raise the crucible to the insulation zone, and use a gradient heating method for liquid phase sintering. The temperature curve is as follows: within 120 minutes, the temperature after cooling from solid phase sintering is raised to 800°C, and the temperature is kept for 60 minutes; within 60 minutes, the temperature is continued to rise to 1300°C, and the temperature is kept for 90 minutes.

[0098] (4) Directional cooling solidification

[0099] After liquid phase sintering is completed, the solidification direction of the material is controlled by adjusting the height of the lifting mechanism. The specific implementation method is as follows:

[0100] The lifting mechanism descends 60mm and remains there for 30 minutes;

[0101] The lifting mechanism continues to descend 50mm and maintains this position for 30 minutes;

[0102] The lifting mechanism continues to descend 60 mm and maintains this position for 60 minutes;

[0103] The lifting mechanism continues to descend by 80 mm, and the prepared rods are taken out as the furnace naturally cools to below 100°C.

[0104] The vacuum degree in the furnace during solidification should be ≤6.1x10 -2 Pa.

[0105] (5) Solution treatment and aging treatment

[0106] First, the prepared bar material was placed in the No. 1 heat treatment furnace for solution treatment at a temperature of 980°C, kept at this temperature for 240 minutes, and then air-cooled with the furnace;

[0107] The rods were then placed in a No. 2 heat treatment furnace for aging treatment at a heating temperature of 480°C and a holding time of 360 minutes. The materials were cooled in the furnace and finally a vacuum switch copper-chromium series contact material with high density, low gas content, strong resistance to ablation and welding was obtained.

[0108] Example 3

[0109] (1) Preparation of materials

[0110] Take Cr powder with a purity of ≥99.50% and a mesh size of 80-200 and W powder with a purity of ≥99.0% and a mesh size of 180-300, mix them in a ratio of 99:1, put the ingredients in a vacuum drying oven, pump the vacuum degree to -0.086MPa, start heating to 85℃, and keep it warm for 3h. Put the dried ingredients into a mixer at a speed of 80r / min, stir and mix for 3h to obtain a mixture.

[0111] (2) Solid phase sintering

[0112] Take a graphite crucible with a diameter of Ф460mm and an aperture of 48mm. The crucible height is 240mm, and the graphite crucible is cleaned. The mixture prepared in step 1 is loaded into the hole of the graphite crucible using a funnel. The loose height is 120mm. The graphite crucible filled with powder is placed on a vibrator with an amplitude set to 3mm and a powder vibration time set to 120s.

[0113] Place the graphite crucible on the rack 4 of the device, turn on the slide valve pump and the Roots pump, and when the vacuum degree is 5.8x10 -2Start heating at Pa, and raise the temperature from room temperature to 250℃ within 60min; continue to raise the temperature from 200℃ to 650℃ within 90min, and keep it warm for 60min; continue to raise the temperature from 650℃ to 950℃ within 90min, and keep it warm for 120min; after heating, lower the lifting mechanism to the cooling zone, and open the furnace door as the furnace naturally cools to below 100℃.

[0114] (3) Liquid phase sintering

[0115] Take an oxygen-free copper rod with a diameter of Ф46 and a material of TU0, cut it into a length of 1 / 2 of the crucible hole depth, wipe the surface of the copper rod clean with alcohol, and place it in a vacuum drying oven for 6 hours at a drying temperature of 60°C. Place the baked copper rod on the fired skeleton, and cover the graphite crucible with graphite paper to prevent copper volatilization. Use a lifting mechanism to raise the graphite crucible to the insulation zone, and use a gradient heating method for liquid phase sintering. The temperature curve is as follows: within 120 minutes, the temperature after cooling from solid phase sintering is raised to 800°C, and the temperature is kept for 60 minutes; within 60 minutes, the temperature is continued to rise to 1300°C, and the temperature is kept for 90 minutes.

[0116] (4) Directional cooling solidification

[0117] After liquid phase sintering is completed, the solidification direction of the material is controlled by adjusting the height of the lifting mechanism. The specific implementation method is as follows:

[0118] The lifting mechanism descends 40 mm and remains there for 40 minutes;

[0119] The lifting mechanism continues to descend 60 mm and maintains this position for 40 minutes;

[0120] The lifting mechanism continues to descend 50 mm and maintains this position for 80 minutes;

[0121] The lifting mechanism continues to descend 100 mm, and the prepared rods are taken out as the furnace naturally cools to below 100°C.

[0122] The vacuum degree in the furnace during solidification should be ≤5x10 -2 Pa.

[0123] (5) Solution treatment and aging treatment

[0124] First, the prepared bar material was placed in the No. 1 heat treatment furnace for solution treatment at a temperature of 920°C, kept at this temperature for 120 minutes, and then air-cooled with the furnace;

[0125] The rods were then placed in a No. 2 heat treatment furnace for aging treatment at a heating temperature of 420°C and a holding time of 180 minutes. The materials were cooled in the furnace and finally a vacuum switch copper-chromium series contact material with high density, low gas content, and strong resistance to ablation and welding was obtained.

[0126] Example 4

[0127] (1) Preparation of materials

[0128] Take Cr powder with a purity of ≥99.50% and a mesh size of 80-200 and W powder with a purity of ≥99.0% and a mesh size of 180-300, mix them according to 99.5:0.5, put the ingredients in a vacuum drying oven, draw the vacuum degree to -0.083MPa, start heating to 85℃, and keep it warm for 3h. Put the dried ingredients into a mixer at a speed of 80r / min, stir and mix for 3h to obtain a mixture.

[0129] (2) Solid phase sintering

[0130] Take a graphite crucible with a diameter of Ф460mm and an aperture of 48mm. The crucible height is 240mm, and the crucible is cleaned. The mixture prepared in step 1 is loaded into the hole of the graphite crucible using a funnel. The loose height is 120mm. The graphite crucible filled with powder is placed on a vibrator with an amplitude set to 3mm and a powder vibration time set to 120s.

[0131] Place the graphite crucible on the rack 4 of the device, turn on the slide valve pump and the Roots pump, and when the vacuum degree is 5.6x10 -2 Start heating at Pa, and raise the temperature from room temperature to 250℃ within 60min; continue to raise the temperature from 200℃ to 650℃ within 90min, and keep it warm for 60min; continue to raise the temperature from 600℃ to 950℃ within 90min, and keep it warm for 120min; after heating, lower the lifting mechanism to the cooling zone, and open the furnace door as the furnace naturally cools to below 100℃.

[0132] (3) Liquid phase sintering

[0133] Take an oxygen-free copper rod with a diameter of 46 and made of TU0, cut it into a length of 1 / 2 of the crucible hole depth, wipe the surface of the copper rod clean with alcohol, and dry it in a vacuum drying oven for 6 hours at a drying temperature of 60°C. Place the baked copper rod on the fired skeleton, and cover the graphite crucible with graphite paper to prevent copper from volatilizing.

[0134] The graphite crucible was raised to the insulation zone by a lifting mechanism, and liquid phase sintering was performed by gradient heating. The temperature curve was as follows: the temperature after cooling from solid phase sintering was raised to 800°C within 120 minutes, and kept warm for 60 minutes; the temperature was further raised to 1300°C within 60 minutes, and kept warm for 90 minutes.

[0135] (4) Directional cooling solidification

[0136] After liquid phase sintering is completed, the solidification direction of the material is controlled by adjusting the height of the lifting mechanism. The specific implementation method is as follows:

[0137] The lifting mechanism descends 50mm and maintains for 30 minutes;

[0138] The lifting mechanism continues to descend 50mm and maintains this position for 30 minutes;

[0139] The lifting mechanism continues to descend by 70 mm and maintains this position for 60 minutes;

[0140] The lifting mechanism continues to descend by 80 mm, and the prepared rods are taken out as the furnace naturally cools to below 100°C.

[0141] The vacuum degree in the furnace during solidification should be ≤6.1x10 -2 Pa.

[0142] (5) Solution treatment and aging treatment

[0143] First, the prepared bar material was placed in the No. 1 heat treatment furnace for solution treatment at a temperature of 980°C, kept at this temperature for 240 minutes, and then air-cooled with the furnace;

[0144] The rods were then placed in a No. 2 heat treatment furnace for aging treatment at a heating temperature of 480°C and a holding time of 360 minutes. The materials were cooled in the furnace and finally a vacuum switch copper-chromium series contact material with high density, low gas content, strong resistance to ablation and welding was obtained.

[0145] Example 5

[0146] (1) Preparation of materials

[0147] Take Cr powder with a purity of ≥99.50% and a mesh size of 80-200 and W powder with a purity of ≥99.0% and a mesh size of 180-300, mix them in a ratio of 99:1, put the ingredients in a vacuum drying oven, pump the vacuum degree to -0.086MPa, start heating to 85℃, and keep it warm for 3h. Put the dried ingredients into a mixer at a speed of 80r / min, stir and mix for 3h to obtain a mixture.

[0148] (2) Solid phase sintering

[0149] Take a graphite crucible with a diameter of Ф460mm and an aperture of 48mm. The crucible height is 240mm, and the crucible is cleaned. The mixture prepared in step 1 is loaded into the hole of the graphite crucible using a funnel. The loose height is 120mm. The graphite crucible filled with powder is placed on a vibrator with an amplitude set to 3mm and a powder vibration time set to 120s.

[0150] Place the graphite crucible on the rack 4 of the device, turn on the slide valve pump and Roots pump, and when the vacuum degree is 5.8x10 -2Start heating at Pa, and raise the temperature from room temperature to 250℃ within 60min; continue to raise the temperature from 200℃ to 650℃ within 90min, and keep it warm for 60min; continue to raise the temperature from 600℃ to 950℃ within 90min, and keep it warm for 120min; after heating, lower the lifting mechanism to the cooling zone, and open the furnace door as the furnace naturally cools to below 100℃.

[0151] (3) Liquid phase sintering

[0152] Take an oxygen-free copper rod with a diameter of 46 and a material of TU0, cut it into a length of 1 / 2 of the crucible hole depth, wipe the surface of the copper rod clean with alcohol, and dry it in a vacuum drying oven for 3 hours at a drying temperature of 85°C. Place the baked copper rod on the fired skeleton, and cover the graphite crucible with graphite paper to prevent copper volatilization. Use a lifting mechanism to raise the crucible to the insulation zone, and use a gradient heating method for liquid phase sintering. The temperature curve is as follows: within 150 minutes, the temperature after cooling from solid phase sintering is raised to 900°C, and the temperature is kept for 90 minutes; within 90 minutes, the temperature is continued to rise to 1480°C, and the temperature is kept for 150 minutes.

[0153] (4) Directional cooling solidification

[0154] After liquid phase sintering is completed, the solidification direction of the material is controlled by adjusting the height of the lifting mechanism. The specific implementation method is as follows:

[0155] The lifting mechanism descends 50mm and remains there for 45 minutes;

[0156] The lifting mechanism continues to descend 50 mm and maintains this position for 45 minutes;

[0157] The lifting mechanism continues to descend 50 mm and maintains this position for 90 minutes;

[0158] The lifting mechanism continues to descend 100 mm, and the prepared rods are taken out as the furnace naturally cools to below 100°C.

[0159] The vacuum degree in the furnace during solidification should be ≤5x10 -2 Pa.

[0160] (5) Solution treatment and aging treatment

[0161] First, the prepared bar material was placed in the No. 1 heat treatment furnace for solution treatment at a temperature of 920°C, kept at this temperature for 120 minutes, and then air-cooled with the furnace;

[0162] The rods were then placed in a No. 2 heat treatment furnace for aging treatment at a heating temperature of 420°C and a holding time of 180 minutes. The materials were cooled in the furnace and finally a vacuum switch copper-chromium series contact material with high density, low gas content, and strong resistance to ablation and welding was obtained.

[0163] Example 6

[0164] (1) Preparation of materials

[0165] Take Cr powder with a purity of ≥99.50% and a mesh size of 80-200 and W powder with a purity of ≥99.0% and a mesh size of 180-300, mix them according to 99.5:0.5, put the ingredients in a vacuum drying oven, pump the vacuum degree to -0.086MPa, start heating to 85℃, and keep it warm for 3h. Put the dried ingredients into a mixer at a speed of 80r / min, stir and mix for 3h to obtain a mixture.

[0166] (2) Solid phase sintering

[0167] Take a graphite crucible with a diameter of Ф460mm and an aperture of 48mm. The crucible height is 240mm, and the crucible is cleaned. The mixture prepared in step 1 is loaded into the hole of the graphite crucible using a funnel. The loose height is 120mm. The graphite crucible filled with powder is placed on a vibrator with an amplitude set to 3mm and a powder vibration time set to 120s.

[0168] Place the graphite crucible on the rack 4 of the device, turn on the slide valve pump and Roots pump, and when the vacuum degree is 5.8x10 -2 Start heating at Pa, and heat from room temperature to 250℃ in 60 minutes; heat from 200℃ to 650℃ in 90 minutes, and keep warm for 60 minutes; heat from 600℃ to 950℃ in 90 minutes, and keep warm for 120 minutes; after heating, lower the lifting mechanism to the cooling zone, and open the furnace door as the furnace cools naturally to below 100℃.

[0169] (3) Liquid phase sintering

[0170] Take an oxygen-free copper rod with a diameter of 46 and a material of TU0, cut it into a length of 1 / 2 of the crucible hole depth, wipe the surface of the copper rod clean with alcohol, and dry it in a vacuum drying oven for 3 hours at a drying temperature of 85°C. Place the baked copper rod on the fired skeleton, and cover the graphite crucible with graphite paper to prevent copper volatilization. Use a lifting mechanism to raise the crucible to the insulation zone, and use a gradient heating method for liquid phase sintering. The temperature curve is as follows: rise to 900°C within 150 minutes, keep warm for 90 minutes; continue to heat up to 1480°C within 90 minutes, and keep warm for 150 minutes.

[0171] (4) Directional cooling solidification

[0172] After liquid phase sintering is completed, the solidification direction of the material is controlled by adjusting the height of the lifting mechanism. The specific implementation method is as follows:

[0173] The lifting mechanism descends 50mm and remains there for 45 minutes;

[0174] The lifting mechanism continues to descend 50 mm and maintains this position for 45 minutes;

[0175] The lifting mechanism continues to descend 50 mm and maintains this position for 90 minutes;

[0176] The lifting mechanism continues to descend 100 mm, and the prepared rods are taken out as the furnace naturally cools to below 100°C.

[0177] The vacuum degree in the furnace during solidification should be ≤5x10 -2 Pa.

[0178] (5) Solution treatment and aging treatment

[0179] First, the prepared bar material was placed in the No. 1 heat treatment furnace for solution treatment at a temperature of 920°C, kept at this temperature for 120 minutes, and then air-cooled with the furnace;

[0180] The rods were then placed in a No. 2 heat treatment furnace for aging treatment at a heating temperature of 420°C and a holding time of 180 minutes. The materials were cooled in the furnace and finally a vacuum switch copper-chromium series contact material with high density, low gas content, and strong resistance to ablation and welding was obtained.

[0181] Example 7

[0182] (1) Preparation of materials

[0183] Take Cr powder with a purity of ≥99.50% and a mesh size of 80-200 and W powder with a purity of ≥99.0% and a mesh size of 180-300, mix them in a ratio of 99:1, put the ingredients in a vacuum drying oven, pump the vacuum degree to -0.086MPa, start heating to 85℃, and keep it warm for 3h. Put the dried ingredients into a mixer at a speed of 80r / min, stir and mix for 3h to obtain a mixture.

[0184] (2) Solid phase sintering

[0185] Take a graphite crucible with a diameter of Ф460mm and an aperture of 48mm. The crucible height is 240mm, and the graphite crucible is cleaned. The mixture prepared in step 1 is loaded into the hole of the graphite crucible using a funnel. The loose height is 120mm. The graphite crucible filled with powder is placed on a vibrator with an amplitude set to 3mm and a powder vibration time set to 120s.

[0186] Place the graphite crucible on the rack 4 of the device, turn on the slide valve pump and Roots pump, and when the vacuum degree is 5.8x10 -2 Start heating at Pa, and raise the temperature from room temperature to 250℃ within 60min; continue to raise the temperature from 200℃ to 650℃ within 90min, and keep it warm for 60min; continue to raise the temperature from 600℃ to 950℃ within 90min, and keep it warm for 120min; after heating, lower the lifting mechanism to the cooling zone, and open the furnace door as the furnace naturally cools to below 100℃.

[0187] (3) Liquid phase sintering

[0188] Take an oxygen-free copper rod with a diameter of 46 and a material of TU0, cut it into a length of 1 / 2 of the crucible hole depth, wipe the surface of the copper rod clean with alcohol, and dry it in a vacuum drying oven for 3 hours at a drying temperature of 85°C. Place the baked copper rod on the fired skeleton, and cover the crucible with graphite paper to prevent copper volatilization. Use a lifting mechanism to raise the graphite crucible to the insulation zone, and use a gradient heating method for liquid phase sintering. The temperature curve is as follows: within 150 minutes, the temperature after cooling from solid phase sintering is raised to 900°C, and the temperature is kept for 90 minutes; within 90 minutes, the temperature is continued to rise to 1480°C, and the temperature is kept for 150 minutes.

[0189] (4) Directional cooling solidification

[0190] After liquid phase sintering is completed, the solidification direction of the material is controlled by adjusting the height of the lifting mechanism. The specific implementation method is as follows:

[0191] The lifting mechanism descends 50mm and remains there for 45 minutes;

[0192] The lifting mechanism continues to descend 60 mm and maintains this position for 45 minutes;

[0193] The lifting mechanism continues to descend 40 mm and maintains this position for 90 minutes;

[0194] The lifting mechanism continues to descend 100 mm, and the prepared rods are taken out as the furnace naturally cools to below 100°C.

[0195] The vacuum degree in the furnace during solidification should be ≤5x10 -2 Pa.

[0196] (5) Solution treatment and aging treatment

[0197] First, the prepared bar material was placed in the No. 1 heat treatment furnace for solution treatment at a temperature of 980°C, kept at this temperature for 240 minutes, and then air-cooled with the furnace;

[0198] The rods were then placed in a No. 2 heat treatment furnace for aging treatment at a heating temperature of 480°C and a holding time of 360 minutes. The materials were cooled in the furnace and finally a vacuum switch copper-chromium series contact material with high density, low gas content, strong resistance to ablation and welding was obtained.

[0199] Example 8

[0200] (1) Preparation of materials

[0201] Take Cr powder with a purity of ≥99.50% and a mesh size of 80-200 and W powder with a purity of ≥99.0% and a mesh size of 180-300, mix them according to 99.5:0.5, put the ingredients in a vacuum drying oven, pump the vacuum degree to -0.086MPa, start heating to 85℃, and keep it warm for 3h. Put the dried ingredients into a mixer at a speed of 80r / min, stir and mix for 3h to obtain a mixture.

[0202] (2) Solid phase sintering

[0203] Take a graphite crucible with a diameter of Ф460mm and an aperture of 48mm. The crucible height is 240mm, and the graphite crucible is cleaned. The mixture prepared in step 1 is loaded into the hole of the graphite crucible using a funnel. The loose height is 120mm. The graphite crucible filled with powder is placed on a vibrator with an amplitude set to 3mm and a powder vibration time set to 120s.

[0204] Place the graphite crucible on the rack 4 of the device, turn on the slide valve pump and Roots pump, and when the vacuum degree is 5.8x10 -2 Start heating at Pa, and raise the temperature from room temperature to 250℃ within 60min; continue to raise the temperature from 200℃ to 650℃ within 90min, and keep it warm for 60min; continue to raise the temperature from 600℃ to 950℃ within 90min, and keep it warm for 120min; after heating, lower the lifting mechanism to the cooling zone, and open the furnace door as the furnace naturally cools to below 100℃.

[0205] (3) Liquid phase sintering

[0206] Take an oxygen-free copper rod with a diameter of 46 and a material of TU0, cut it into a length of 1 / 2 of the crucible hole depth, wipe the surface of the copper rod clean with alcohol, and dry it in a vacuum drying oven for 3 hours at a drying temperature of 85°C. Place the baked copper rod on the fired skeleton, and cover the crucible with graphite paper to prevent copper volatilization. Use a lifting mechanism to raise the graphite crucible to the insulation zone, and use a gradient heating method for liquid phase sintering. The temperature curve is as follows: within 150 minutes, the temperature after cooling from solid phase sintering is raised to 900°C, and the temperature is kept for 90 minutes; within 90 minutes, the temperature is continued to rise to 1480°C, and the temperature is kept for 150 minutes.

[0207] (4) Directional cooling solidification

[0208] After liquid phase sintering is completed, the solidification direction of the material is controlled by adjusting the height of the lifting mechanism. The specific implementation method is as follows:

[0209] The lifting mechanism descends 50mm and remains there for 45 minutes;

[0210] The lifting mechanism continues to descend 50 mm and maintains this position for 45 minutes;

[0211] The lifting mechanism continues to descend 50 mm and maintains this position for 90 minutes;

[0212] The lifting mechanism continues to descend 100 mm, and the prepared rods are taken out as the furnace naturally cools to below 100°C.

[0213] The vacuum degree in the furnace during solidification should be ≤5x10 -2 Pa.

[0214] (5) Solution treatment and aging treatment

[0215] First, the prepared bar material was placed in the No. 1 heat treatment furnace for solution treatment at a temperature of 920°C, kept at this temperature for 120 minutes, and then air-cooled with the furnace;

[0216] The rods were then placed in a No. 2 heat treatment furnace for aging treatment at a heating temperature of 420°C and a holding time of 180 minutes. The materials were cooled in the furnace and finally a vacuum switch copper-chromium series contact material with high density, low gas content, strong resistance to ablation and welding was obtained.

[0217] The eight materials prepared in Examples 1-8 of the present invention were subjected to performance tests. As shown in Table 1, the performance results all met the index requirements of CuCr(50) in the "Technical Requirements for Copper-Chromium Electrical Contacts".

[0218] Table 1 Test results of material properties prepared by Examples 1-8

[0219]

[0220] By comparing the test performance of the materials prepared in Example 1 and Example 2, it can be seen that the higher the W content, the higher the hardness of the contact material, but the conductivity is slightly reduced;

[0221] Comparing the material performance test results of Examples 3 and 4 with those of Examples 1 and 2, it is found that increasing the skeleton sintering temperature and extending the holding time can reduce the gas content of the prepared material;

[0222] The test results of Examples 5 and 6 show that increasing the infiltration temperature can increase the density of the material.

[0223] From the results of the material performance tests of Example 7 and Example 8, it can be seen that increasing the solution and aging temperatures is helpful to improve the hardness of the material.

[0224] It can be seen from Table 1 that the copper-chromium series contact material of the vacuum switch prepared by the present invention has strong pressure resistance, ablation resistance and low gas content, good pressure resistance and ablation resistance, and high hardness.

[0225] The reason for adding W element to the copper-chromium series contact material of the vacuum switch prepared by the present invention is that W element itself has a high melting point (3410°C), and the addition of W element can limit the growth of Cr particles, thereby achieving the purpose of refining particles and improving the ablation resistance of the contact material.

[0226] In the process of preparing materials by a single liquid phase sintering process, the high melting point component of chromium tungsten is not melted, resulting in a low Gibbs free energy of the chromium tungsten component; while the preparation process of the present invention is to first sinter the chromium tungsten skeleton and then infiltrate copper, which belongs to the solid-liquid sintering method. The Gibbs free energy of the chromium tungsten component is greater than the chromium tungsten component prepared by a single liquid phase sintering method, so the probability of contact material welding is reduced during use. Furthermore, from the perspective of adding trace tungsten elements, the melting point of tungsten elements is above 3400°C, which is much higher than the melting point of chromium elements at 1800°C. Therefore, the addition of high melting point elements can improve the ablation resistance and welding resistance of the material.

[0227] The present invention adopts a furnace body 1 with a lifting mechanism, which gradually descends from the heating and heat preservation zone to the cooling zone, so that the copper liquid gradually solidifies from the bottom to the top during the solidification process. The innovation lies in that copper has a large shrinkage and is very likely to have shrinkage holes during the solidification process. If the upper part is not replenished with copper liquid in time, the density of the prepared material will be poor and there will be chromium holes. The present invention adopts a lifting mechanism to form a temperature gradient between the top and the bottom of the chromium-tungsten skeleton. The purpose is to replenish the liquid at the top when shrinkage holes appear at the bottom, so that the density of the prepared material will be greatly improved and the internal defects will be reduced.

[0228] The present invention greatly improves the pressure resistance, ablation resistance and ablation resistance of the contact material through the solid-liquid sintering process, directional cooling solidification technology and the addition of trace element W. The copper-chromium contact material prepared by the preparation process of the present invention has greatly improved pressure resistance and ablation resistance, and can be applied to vacuum switches with voltage levels of 72.5KV-252KV; the gas content of the contact material prepared by the present invention is much lower than that of the contact material prepared by other processes, so that the insulation of the vacuum switch is further improved.

[0229] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A preparation process for copper-chromium series contact materials of vacuum switches. It is characterized in that The following steps are involved: (1) Mixing: In a vacuum environment, Cr powder and W powder are mixed into a mixture; wherein the Cr powder and W powder are mixed according to the weight percentage of Cr powder 99.0% to 99.5% and W powder 0.5% to 1%; (2) Solid-phase sintering: The mixed material is subjected to solid-phase sintering treatment and then naturally cooled to obtain a chromium-tungsten skeleton; wherein the solid-phase sintering treatment adopts a gradient temperature increase; (3) Liquid phase sintering: placing an oxygen-free copper rod on a chromium-tungsten skeleton and performing liquid phase sintering treatment to allow the copper liquid to infiltrate the chromium-tungsten skeleton to obtain a copper-infiltrated chromium-tungsten material; wherein the liquid phase sintering treatment adopts a gradient temperature increase; (4) Directional cooling and solidification: gradually reduce the cooling temperature of the copper-chromium-tungsten infiltrated material, forming a gradient temperature field distribution in which the temperature gradually decreases from the top to the bottom of the copper-chromium-tungsten infiltrated material; at the same time, the copper liquid above the copper-chromium-tungsten infiltrated material continues to flow from the top to the bottom, so that the copper liquid gradually solidifies from the bottom to the top; (5) Subsequent treatment: The material after the cooling and solidification treatment in step (4) is subjected to solution treatment and aging treatment in sequence to obtain a vacuum switch copper-chromium series contact material.

2. The preparation process of the copper-chromium series contact material of a vacuum switch according to claim 1, It is characterized in that In step (1), when preparing Cr powder and W powder, the ingredients are first dried under vacuum conditions, and then the dried ingredients are mixed and stirred to obtain a mixture.

3. The preparation process of the copper-chromium series contact material of a vacuum switch according to claim 1, It is characterized in that In step (2), the solid phase sintering process adopts a gradient temperature increase, and the specific operation is as follows: Raise the temperature from room temperature to 200-250°C within 45-60 minutes; continue to raise the temperature to 600-650°C within 60-90 minutes, and keep it warm for 45-60 minutes; continue to raise the temperature to 850-950°C within 60-90 minutes, and keep it warm for 90-120 minutes.

4. The preparation process of the copper-chromium series contact material of a vacuum switch according to claim 1, It is characterized in that In step (2), during the solid phase sintering process, the vacuum degree is required to be ≤10 -1 Pa.

5. The preparation process of the copper-chromium series contact material of a vacuum switch according to claim 1, It is characterized in that In step (3), the liquid phase sintering process adopts a gradient temperature increase, and the specific operation is as follows: The temperature after cooling from solid phase sintering is raised to 800-900°C within 120-150 minutes, and kept at this temperature for 60-90 minutes; the temperature is further raised to 1300-1480°C within 60-90 minutes, and kept at this temperature for 90-150 minutes.

6. The preparation process of the copper-chromium series contact material of a vacuum switch according to claim 1, It is characterized in that In step (4), the vacuum degree during cooling and solidification is required to be ≤5x10 -2 Pa.

7. The preparation process of the copper-chromium series contact material of a vacuum switch according to claim 1, It is characterized in that In step (5), the specific operation of the solution treatment is: The solution temperature is 920-980℃, the holding time is 120-240min, and air cooling is used.

8. The preparation process of the copper-chromium series contact material for a vacuum switch according to claim 1, It is characterized in that In step (5), the specific operation of the aging treatment is: The aging temperature is 420-480℃, the holding time is 180-360min, and the cooling is done in air.

9. The copper-chromium series contact material for vacuum switches prepared by the preparation process according to any one of claims 1 to 8, It is characterized in that The density of the copper-chromium series contact material of the vacuum switch is 7.95-8.05 g / cm 3 The average hardness is 85-108HB, the conductivity is 16.3-22.4MS / m, and the density is over 99%.